Coherence, Truth and Testimony - Gähde, Ulrich; Hartmann, Stephan (Springer Netherlands : Imprint: Springer, 2005)
Coherence is a burgeoning topic of research. Diverse methodologies have been applied to shed light on the topic and its relevance to fundamental questions throughout philosophy. The collection brings together the full scope of this research in a single volume. The first group of essays attack the core topic of the book: coherence. Authors in this section take up the challenging and controversial task of measuring the coherence of an information set, while others criticize this endeavor. The second group of papers in the collection relate this foundational research to a wide array of epistemological and metaphysical challenges. For example, some papers consider the relationship between truth and coherence. Is coherence truth conducive, and if yes, under which conditions? A related issue taken up in this volume is the connection between coherence and testimony. Are we justified in believing coherent reports by independent, though only partially reliable witnesses more than a single report? If yes, under which conditions does this claim hold true? By the end of the book, the reader should have a comprehensive understanding of topic of coherence, the controversy surrounding it, and its implications across the discipline of philosophy.